Electromagnetic filter for H⁻ separation from pig with metal hydride cathode - Sereda, I.N.; Tseluyko, A.F.; Ryabchikov, D.L.; Hrechko, Ya.O.; Krupka, A. (Вопросы атомной науки и техники, 2018)
The paper proposes a design and method for calculating an electromagnetic filter for separation of negative hydrogen ions extracted in the longitudinal direction from the Penning discharge with a metal hydride cathode. The design of the filter was calculated on the basis of preliminary experimental data and analysis of the trajectory of charged particles, which were obtained by the numerical solution of motion equation. It has been built a model that allows to choose the optimal external parameters for effective separation of H⁻ ions and the interpretation of subsequent experiments. An experimental test of the model has been performed Пропонується конструкція і методика розрахунку електромагнітного фільтра, призначеного для сепарації негативних іонів водню, видобутих у поздовжньому напрямку з розряду Пеннінга з металогідридним катодом. Розрахунок конструкції фільтра проводився на підставі попередніх експериментальних даних та аналізу траєкторії заряджених частинок, які були розраховані шляхом чисельного рішення рівняння руху. Побудована модель, що дозволяє вибирати оптимальні зовнішні параметри для ефективної сепарації іонів Н⁻ і інтерпретації наступних експериментів. Проведена експериментальна перевірка працездатності побудованої моделі. Предлагается конструкция и методика расчета электромагнитного фильтра, предназначенного для сепарации отрицательных ионов водорода, извлекаемых в продольном направлении из разряда Пеннинга с металлогидридным катодом. Расчет конструкции фильтра проводился на основании предварительных экспериментальных данных и анализа траектории заряженных частиц, которые были рассчитаны путем численного решения уравнения движения. Построена модель, позволяющая выбирать оптимальные внешние параметры для эффективной сепарации ионов Н⁻ и интерпретации последующих экспериментов. Проведена экспериментальная проверка работоспособности построенной модели.